Republic of Tajikistan : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This report provides the IMF's projections and estimates on Tajikistan's basic data; nominal and real GDP; nominal GDP by sector of origin; fuel consumption; production and yield of major agricultural crops; registered unemployment; sectoral output, employment and productivity; state budget by national classification of revenues and expenditures; operations of the consolidated general government; balance of payments; external debt during 1995-2000; monetary survey; accounts of the national bank of Tajikistan; average annual interest rates during 1998-2000; consumer price index; wholesale price index; credit to the economy from commercial banks during 1997-2000, and so on.